2003
DOI: 10.1063/1.1609982
|View full text |Cite
|
Sign up to set email alerts
|

Chaotropic effect and preferential binding in a hydrophobic interaction model

Abstract: Chaotropic substances such as urea and guanidinium chloride, which tend to increase the solubility of hydrophobic particles in aqueous solutions, are used frequently to destabilize aggregations of nonpolar solute particles and micelles, or to denature proteins. Their important applications have generated a growing interest in the physical origin of the chaotropic effect, which to date remains unclear. In this study, the two-state Muller–Lee–Graziano model for water is adapted to describe the ternary system of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 58 publications
0
26
0
Order By: Relevance
“…[36]. Here we provide only a brief review of the results of this analysis, with emphasis on the differences and similarities in comparison with the kosmotropic effect, which we have discussed at greater length in Sec.…”
Section: Chaotropic Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…[36]. Here we provide only a brief review of the results of this analysis, with emphasis on the differences and similarities in comparison with the kosmotropic effect, which we have discussed at greater length in Sec.…”
Section: Chaotropic Effectmentioning
confidence: 99%
“…The adapted MLG model has been extended to provide a minimal model for the study of chaotropic phenomena in ternary water/solute/cosolvent systems [36] shown that this framework yields a successful description of preferential binding, and of the resulting destabilisation of aggregates of solute particles as a consequence of the role of chaotropic cosolvents in reducing the formation of water structure. We begin with a brief review of the model to summarise its physical basis and to explain the modifications required for the inclusion of cosolvent effects.…”
Section: Model a Hydrophobic-polar Modelmentioning
confidence: 99%
“…The respective degeneracies, normalized to a non-degenerate ordered shell conformation, are taken to be q ds = 49, q db = 40, q ob = 10 and q os = 1 [31]. These relative values have been found to be appropriate for reproducing the phenomenology of hydrophobic interactions [22,31], protein denaturation [33,34], swelling of biopolymers [35], and cosolvent effects on solubility of hydrophobic particles [23,36]. Precise values of the microscopic parameters may in fact be refined by comparison with experimental measurements to yield semi-quantitative agreement for different solutions [22,31,35,36].…”
Section: A Water Structurementioning
confidence: 99%
“…Full details of the foundations and qualitative properties of the model can be found in Refs. [22] and [23].…”
Section: A Water Structurementioning
confidence: 99%
See 1 more Smart Citation